Money Illusion and Housing Frenzies - Brunnermeier, Markus K.; Julliard, Christian (Review of Financial Studies, 2008)
A reduction in in ation can fuel run-ups in housing prices if people suer from money illusion. For example, investors who decide whether to rent or buy a house by simply comparing monthly rent and mortgage payments do not take into account the fact that in ation lowers future real mortgage costs. We decompose the price-rent ratio into a rational component -meant to capture the "proxy eect" and risk premia -and an implied mispricing. We nd that in ation and nominal interest rates explain a large share of the time-series variation of the mispricing, and that the tilt eect is very unlikely to rationalize this nding.